If It Is Life We Want: A Prayer for the Future (of the) University - Moser, Susanne C.; Fazey, Ioan (Frontiers in Sustainability, 2021)
Universities are one potentially important place – albeit not the only one – to initiate the next generation into becoming the adult humans needed to navigate the difficult future of the Anthropocene. The university of the future will fail this mission, if it only prepared young people in the technical expertise required to manage accelerating climate crises and the breakdown of Earth’s life support and interlocking human systems. The depth and extent of transformation that awaits society requires people skilled in coping emotionally and in effectively engaging the plethora of challenges ahead with agility, creativity, resolve, vision and integrity. It requires universities themselves to transform into institutions of human development that cease to participate, pardon and propagate patterns of exploitation and, instead, become singularly dedicated to restoring and regenerating the conditions for life. This paper articulates a vision of a radically different future “university”. Building on others’ calls for transformation-supporting education, we frame universities’ role in the larger arc of inner and outer human and societal development. We spell out some of the implications and needs such a shift would entail. The paper is written in the spirit of the future university that we envision: not just from our analytical thinking brain, but drawing also on our imaginative/intuitive, emotional, and sensing/embodied ways of knowing. As such, it breaks with conventional academic writing and opens up wider possibilities for and commitment to life-affirming and restorative action.